Queer lives in American music: Bernstein, Blitzstein, and Copland - Stevens, Colby Reuben (Kansas State University, 2024)
In the last half century, there has been an increase in gender studies within the realm of musicology. Thus far, most of the research that has been conducted centers on how composers’ queerness is manifested in their music. The works of notable composers such as Peter Tchaikovsky, Aaron Copland, Benjamin Britten, and Francis Poulenc have been analyzed thoroughly. It is inherent that these composers’ musical language is varied, and thus the musical manifestation of their queerness is varied. Studies on the impact of LGBTQIA+ culture (or lack thereof) on queer composers’ lives is limited. This research serves as an examination of the intersectionality of select queer American composers within the early to middle twentieth century. This study is a focus on the lives of composers Aaron Copland, Marc Blitzstein, and Leonard Bernstein through the lens of the queer culture of their time. This research serves to illuminate these composers’ lives in a way that has not been previously emphasized. The purpose of this research is to explore the lives of three queer American composers and how they were impacted by queer culture of their time.
Keywords: Aaron Copland; Marc Blitzstein; Leonard Bernstein; Queer; American; Composer